Nationalist Ethnicities as Religious Identities: Islam, Buddhism, and Citizenship in Myanmar by Imtiyaz Yusuf (American Journal of Islam and Society, 2017)
For centuries, the Rohingya have been living within the borders of the countryestablished in 1948 as Burma/Myanmar. Today left stateless, having beengradually stripped of their citizenship rights, they are described by theUnited Nations as one of the most persecuted minorities in the world. Inorder to understand the complexity of this conflict, one must consider howBurma is politically transitioning from military to democratic rule, a processthat is open (much as was Afghanistan) to competition for resources by internationaland regional players such as the United States, China, India, Israel,Japan, and Australia.1 To be fair, the record of Southeast Asian Muslimcountries with Buddhist minorities is also not outstanding. Buddhist minoritiesidentified as ethnic groups have faced great discrimination in, amongothers, Bangladesh, Malaysia, Indonesia, and Brunei ...